Mutually constructive roles of Ail and LPS in Yersinia pestis serum survival - Singh, Chandan (Mol Microbiol, 2020)
The outer membrane is a key virulence determinant of gram‐negative bacteria. In Yersinia pestis, the deadly agent that causes plague, the protein Ail and lipopolysaccharide (LPS)(6) enhance lethality by promoting resistance to human innate immunity and antibiotics, enabling bacteria to proliferate in the human host. Their functions are highly coordinated. Here we describe how they cooperate to promote pathogenesis. Using a multidisciplinary approach, we identify mutually constructive interactions between Ail and LPS that produce an extended conformation of Ail at the membrane surface, cause thickening and rigidification of the LPS membrane, and collectively promote Y. pestis survival in human serum, antibiotic resistance, and cell envelope integrity. The results highlight the importance of the Ail–LPS assembly as an organized whole, rather than its individual components, and provide a handle for targeting Y. pestis pathogenesis.